Implementation of Inquiry Learning Model Can Improve Learning Outcomes of Students' Pillars of Faith Material at MIS Sabilul Muttaqin Tlanakan Pamekasan - Yatimah; Kholifah, Yeni; Puteri, Yayuk Sri Rahma; Royani, Yayan; Yanti, Yeyen (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to analyze the effectiveness of the application of the inquiry learning model in improving the learning outcomes of grade 1 students on the material of the Pillars of Faith at MIS Sabilul Muttaqin Tlanakan Pamekasan. The inquiry learning model is an approach that emphasizes the active involvement of students in the learning process through exploration, investigation, and independent discovery of concepts. This model is considered to be able to improve students' understanding of the material being taught and develop their critical thinking skills and curiosity. This study uses a classroom action research (CAR) method consisting of two cycles, where each cycle involves the stages of planning, implementation, observation, and reflection. The subjects of the study were grade 1 students of MIS Sabilul Muttaqin Tlanakan Pamekasan with a total of 25 students. Data were collected through learning outcome tests, observations of student and teacher activities, and documentation. Data analysis was carried out using quantitative and qualitative descriptive techniques to see the increase in student learning outcomes after the application of the inquiry learning model. The results showed that the application of the inquiry learning model significantly improved student learning outcomes on the material of the Pillars of Faith. In the first cycle, the average score of students increased compared to before the application of the inquiry model, although there were still some students who had not reached the Minimum Completion Criteria (KKM). After improvements were made in the second cycle, learning outcomes increased further, with most students successfully achieving or exceeding the set KKM. In addition, observations showed that students became more active, enthusiastic, and motivated in following the learning process. The application of the inquiry learning model also had a positive impact on students' critical thinking skills. They were better able to ask questions, connect concepts, and find their own answers through exploration and discussion processes. Teachers also experienced improvements in their classroom management skills and provided guidance that was appropriate to students' needs. Thus, this study confirms that the inquiry learning model can be an effective alternative in improving student learning outcomes, especially in Islamic Religious Education learning at the elementary level. In conclusion, the inquiry learning model has been proven to improve the learning outcomes of grade 1 students on the material of the Pillars of Faith at MIS Sabilul Muttaqin Tlanakan Pamekasan. Therefore, it is recommended for educators to apply this approach in learning to increase active involvement of students and strengthen their understanding of the material being taught. In addition, further research can be conducted with a wider scope to identify the effectiveness of this model in various subjects and different levels of education